2008
DOI: 10.1007/s00253-008-1472-8
|View full text |Cite
|
Sign up to set email alerts
|

Uricase production by a recombinant Hansenula polymorpha strain harboring Candida utilis uricase gene

Abstract: Uricase is an important medical enzyme which can be used to determine urate in clinical analysis, to therapy gout, hyperuricemia, and tumor lysis syndrome. Uricase of Candida utilis was successfully expressed in Hansenula polymorpha under the control of methanol oxidase promoter using Saccharomyces cerevisiae α-factor signal peptide as the secretory sequence. Recombinant H. polymorpha MU200 with the highest extracellular uricase production was characterized with three copies of expression cassette and selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 36 publications
(38 reference statements)
0
20
1
Order By: Relevance
“…The highest production of recombinant uricase reached 52.3 U/mL (about 2.1 g/L of protein) extracellularly and 60.3 U/mL (about 2.4 g/L of protein) intracellularly in fed-batch fermentation after 58 h of incubation, which are much higher than those expressed in other expression systems [134].…”
Section: Genetics and Uricase Encoding Genesmentioning
confidence: 78%
“…The highest production of recombinant uricase reached 52.3 U/mL (about 2.1 g/L of protein) extracellularly and 60.3 U/mL (about 2.4 g/L of protein) intracellularly in fed-batch fermentation after 58 h of incubation, which are much higher than those expressed in other expression systems [134].…”
Section: Genetics and Uricase Encoding Genesmentioning
confidence: 78%
“…According to Chen et al, the only appropriate amount of urate oxidase expression in yeast has been achieved in H. polymorpha (Chen et al 2008). In their report, the Candida utilis urate oxidase was expressed by H. polymorpha and α-MF signal sequence of S. cerevisiae was used to secret the protein.…”
Section: Discussionmentioning
confidence: 99%
“…It was studied that 3% inoculum was used for the optimum production of parent and mutant derived enzyme. Reference [3] optimized the parameters and showed that inoculum size had great influence on the production of urate oxidase.…”
Section: Comparison Of Different Carbon Sourcesmentioning
confidence: 99%
“…The substrate (urate) tightly binds to the one subunit of the enzyme by interaction with arginine (Arg180), leucine (Leu222) and glutamine (Gln223) while to the other subunit with threonine (Thr67) and aspartate (Asp68) [1] , [2]. The solubility of uric acid in the body is considered to be poor as compare to the allantoin [3] , [4]. According to previous studies, it was considered that urate oxidase has copper at its active site but later on it was proved that when this enzyme was isolated from Bacillus subtilis and Aspergillus flavus, contain no copper [5].…”
Section: Introductionmentioning
confidence: 99%